THE MAROSOK TRADITION AS AN EDUCATIONAL MEDIUM FOR LIVESTOCK BUSINESS ETHICS AND TRUST-BASED MARKETING: AN INTERCULTURAL LEARNING APPROACH - Suhardi, Suhardi; Widiarta, I Putu Gede Didik; Qamara, Cori; Azzahra, Jasmine (Universitas Padjadjaran, 2026)
The Marosok tradition is a trust-based livestock trading system of the Minangkabau community, serving as a culturally rooted medium for teaching business ethics and marketing models. This program was conducted under the International Summer School at Mulawarman University and aimed to enhance participants’ understanding of ethical negotiation, local wisdom, and its relevance to contemporary markets. A total of 38 students, comprising 25 international and 13 local students representing diverse academic disciplines, participated in a series of activities, including orientation, thematic lectures, intercultural discussions, role-play simulations, and reflective evaluations. Using a participatory and qualitative-descriptive approach, data were collected through pre- and post-tests, Likert-scale questionnaires, and focus group discussions, and analyzed using descriptive statistics and thematic interpretation. Results indicated a 34.9% increase in participants’ knowledge, particularly in understanding Marosok’s historical context, ethical principles, and non-verbal negotiation mechanisms. With 86% reporting high or very high interest, this increase was primarily attributed to the cultural uniqueness and practical applicability of the material. The multicultural composition of the cohort enriched dialogue, fostered cross-cultural understanding, and stimulated critical reflection on integrating traditional values into modern business contexts. Despite these achievements, challenges included participants’ varying baseline knowledge, limited exposure to trust-based trade systems, and the short duration of the program. It is recommended that future programs extend opportunities for practice, incorporate digital learning tools, and explore applications of Marosok principles in contemporary market platforms to strengthen cultural preservation and educational impact.Tradisi Marosok merupakan sistem perdagangan ternak berbasis kepercayaan dalam komunitas Minangkabau, yang berfungsi sebagai medium budaya untuk mengajarkan etika bisnis dan model pemasaran. Program ini dilaksanakan dalam kerangka International Summer School di Universitas Mulawarman dengan tujuan meningkatkan pemahaman peserta mengenai negosiasi etis, kearifan lokal, serta relevansinya dengan pasar kontemporer. Sebanyak 38 mahasiswa yang terdiri dari 25 mahasiswa internasional dan 13 mahasiswa lokal dari berbagai disiplin ilmu berpartisipasi dalam rangkaian kegiatan, meliputi orientasi, materi tematik, diskusi lintas budaya, simulasi peran, dan evaluasi reflektif. Dengan menggunakan pendekatan partisipatif dan kualitatif-deskriptif, data dikumpulkan melalui pre-test dan post-test, kuesioner skala Likert, serta diskusi kelompok terfokus (FGD), kemudian dianalisis dengan statistik deskriptif dan interpretasi tematik. Hasil penelitian menunjukkan adanya peningkatan pengetahuan sebesar 34,9%, khususnya dalam memahami konteks historis Marosok, prinsip-prinsip etika, dan mekanisme negosiasi non-verbal. Sebanyak 86% peserta menyatakan minat tinggi atau sangat tinggi, yang terutama dipengaruhi oleh keunikan budaya dan relevansi praktis dari materi. Komposisi multikultural peserta memperkaya dialog, memperkuat pemahaman lintas budaya, serta mendorong refleksi kritis mengenai integrasi nilai-nilai tradisional ke dalam konteks bisnis modern. Meskipun demikian, terdapat sejumlah tantangan, antara lain perbedaan pengetahuan dasar peserta, keterbatasan paparan terhadap sistem perdagangan berbasis kepercayaan, serta durasi program yang relatif singkat. Oleh karena itu, disarankan agar program di masa mendatang memperluas kesempatan praktik, mengintegrasikan perangkat pembelajaran digital, serta mengeksplorasi penerapan prinsip-prinsip Marosok dalam platform pasar kontemporer untuk memperkuat pelestarian budaya dan dampak edukatif.